THE EFFECT OF DIGITAL MARKETING ON THE PERFORMANCE AND SUSTAINABILITY OF FOOD MSMES IN JAKARTA DURING THE COVID-19 PANDEMIC - Kaban, Reny Fitriana; Hania, Ilfatul; Widjaja, Hidajat Sofyan; Lubis, Zurlina (Fakultas Ekonomi Universitas IBA, 2024)
The Covid-19 pandemic had an unexpected impact to the global economy, especially in the marketing sector. In the digital era that currently dominates with the help of devices or network technology devices, MSME operators adopt the use of marketing online as a solution for government regulation to minimize direct contact during pandemic. Unfortunately, not all MSMEs have taken advantage of digital tools business, especially in marketing. This study aims to determine the effect of digital marketing on the performance and sustainability of food MSMEs which are comprehensively reviewed. The population in this study were 100 Food MSMEs in DKI Jakarta Province with a maximum turnover of Rp. 10 billion and maximum assets of Rp. 5 billion. This study uses a quantitative method with a type of association study that aims to determine the effect or relationship between variables. By using Partial Least Square as a data processing and analysis technique. The research results show that online marketing contributes 40.3% to SMEs performance and 33.6% to MSMEs sustainability. It is recommended for MSMEs actors to maximize the use of digital marketing in any available platforms in order to increase their performance and maintain their sustainability.